Mechanisms of applied ijtihad in contemporary issues – Enjoining good and forbidding evil as a model - En-Nasry, Hicham (Journal of Islamic Sciences, 2022)
This scientific paper aimed at shedding light on the positive and negative impact of understanding Islamic law on the contemporary Islamic reality, by clarifying the jurisprudential mechanisms that lead to the safety of the application of legal rulings on contemporary issues, and relied on the descriptive analytical approach and the historical method, to analyze and discuss This research consists of three sections: the first to clarify the realization of the mandate in contemporary applied ijtihad, the second about the consideration of outcomes and assessment of behavior when applying provisions, and the third to talk about the impact of contemporary reality on the application of rulings, and all of this is in an application to the issue of enjoining good and forbidding evil as a model as they The axis of reform in the Islamic system. And I reached several results, the most prominent of which are: that the structural ijtihad differs from the applied ijtihad, and that the latter is only performed by those who are qualified scientifically and intellectually, in order to attract interests and repel evils according to the purposes of Islamic Sharia, and that the events that the Islamic world has recently experienced in An attempt to change and reform by enjoining good and forbidding evil necessitates drawing lessons, by evaluating some of the jurisprudential opinions that made events in the field.